2004
DOI: 10.1111/j.1468-1331.2004.00840.x
|View full text |Cite
|
Sign up to set email alerts
|

Water drinking in the management of orthostatic intolerance due to orthostatic hypotension, vasovagal syncope and the postural tachycardia syndrome

Abstract: Water drinking recently has been shown to raise blood pressure in normal subjects and in patients with autonomic failure who have orthostatic hypotension. However, in normal young subjects, ingestion of approximately 500 ml has no pressor effect; but in older subjects there is an increase in blood pressure. An even greater rise in blood pressure occurs in cases with autonomic failure. The possible mechanisms responsible for the pressor response to water include neural and humoral factors; fluid redistribution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
49
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(55 citation statements)
references
References 26 publications
4
49
0
2
Order By: Relevance
“…The mechanism by which it increases blood pressure (BP) is thought to be increased sympathetic tone. 38 Present evidence suggests that both higher IOP and increase in BP may result from increased peripheral vascular resistance, along with a minor reduction in plasma osmolality. [39][40][41][42] It is now known that the thickness of the choroid is altered by changes in BP and IOP.…”
mentioning
confidence: 78%
“…The mechanism by which it increases blood pressure (BP) is thought to be increased sympathetic tone. 38 Present evidence suggests that both higher IOP and increase in BP may result from increased peripheral vascular resistance, along with a minor reduction in plasma osmolality. [39][40][41][42] It is now known that the thickness of the choroid is altered by changes in BP and IOP.…”
mentioning
confidence: 78%
“…Indeed, this is not the most important consequence of the water ingestion on dysautonomic patients. When water is drunk, a pressor response is observed, reaching the maximum effect around 20 min after the ingestion [12,13]. This consequence was demonstrated in older normal subjects and in patients with autonomic failure.…”
Section: Salt and Watermentioning
confidence: 81%
“…It was observed that water ingestion increased orthostatic tolerance to head--up tilt test combined with lower body negative pressure [12]. Its effect alone in vasovagal syncope remains unclear but, in the postural orthostatic tachycardia syndrome, water ingestion attenuates the postural rise in heart rate (HR) and in patients with autonomic failure, and also reduces the degree of orthostatic and postprandial hypotension [13].…”
Section: Salt and Watermentioning
confidence: 99%
“…Water drinking has been recognized as a powerful treatment for orthostatic and postprandial hypotension in patients by virtue of its profound pressor response. 11,30 Oral water intake also has effects on BP and HR in normal subjects, although the actions are more subtle. 13,31 The water-induced pressor response appears to be mediated through sympathetic nervous activation.…”
Section: Discussionmentioning
confidence: 99%